Inside Barefoot Economics - Kletzka, Patrick (Logos Verlag Berlin, 2021)
``... the practice of barefoot economics requires more than simply the lived experience of poverty-related phenomena. In contrast to the prevailing positivist paradigm within the scientific discipline of economics that tends to cultivate particular ways of economic thinking by taking their linguistic presuppositions for granted, barefoot economics involves challenging one's own horizon of possibility for economic thought by putting commonly accepted academic jargon in abeyance.''